Reinforcement Foundations of a Function-Based Behavioral Approach for Students With Challenging Behavior. (August 2020) - Sugai, George; Simonsen, Brandi
This article provides an overview of how reinforcement serves as the foundation for a function-based approach to support students with challenging behavior. Understanding reinforcement is essential when providing function-based support for students with challenging behavior. Reinforcement "strengthens" behavior, increasing the probability that similar behaviors occur again. By understanding and using reinforcement accurately, educators conduct efficient functional behavioral assessments; develop and implement positive, aligned, and individualized behavior support plans; and avoid misrules and misconceptions about reinforcement.